PHYLOGENETIC CHARACTERIZATION OF PSYCHROPHILIC ° BACTERIA ISOLATED FROM DEEP-SEA WATER OF THE NANKAI TROUGH - Ocky Karna Radjasa; Kumiko Kita-Tsukamotoz; Hidetoshi Urakawal; Kouichi Ohwadai (JOURNAL OF COASTAL DEVELOPMENT, 2001)
A screening among 4"C-culturable isolates obtainedfom dcep~sea water of Nankai Trough from a depth of approximately 4,000 m resulted in a total of 5 psychrophilic bacteria showing no growth at 20° C. Phylogenetic characterization based on l6S ribosomal DNA sequence analysis showed that the isolates belonged to the genus Colwellia, Moritella, and CNPT-3, which could be assigned to Psychromonas.